Mining the deep Red-Sea brine pool microbial community for anticancer therapeutics - Luke Esau; Guishan Zhang; Sunil Sagar; Ulrich Stingl; Vladimir B. Bajic; Mandeep Kaur (BMC, 2019)
Abstract Background Microbial species in the brine pools of the Red Sea and the brine pool-seawater interfaces are exposed to high temperature, high salinity, low oxygen levels and high concentrations of heavy metals. As adaptations to these harsh conditions require a large suite of secondary metabolites, these microbes have a huge potential as a source of novel anticancer molecules. Methods A total of 60 ethyl-acetate extracts of newly isolated strains from extreme environments of the Red-Sea were isolated and tested against several human cancer cell lines for potential cytotoxic and apoptotic activities. Results Isolates from the Erba brine-pool accounted for 50% of active bacterial extracts capable of inducing 30% or greater inhibition of cell growth. Among the 60 extracts screened, seven showed selectivity towards triple negative BT20 cells compared to normal fibroblasts. Conclusion In this study, we identified several extracts able to induce caspase-dependent apoptosis in various cancer cell lines. Further investigations and isolation of the active compounds of these Red Sea brine pool microbes may offer a chemotherapeutic potential for cancers with limited treatment options.